Clubhead presentation and spin control capability of elite golfers - Corke, T. W.; Betzler, N. F.; Wallace, E. S.; Otto, S. R. (Procedia Engineering, 2013)
The current study aimed to establish whether or not elite amateur golfers are able to manipulate the magnitude of spin imparted on short iron shots whilst maintaining the same total shot distance. Seven elite male golfers were each asked to hit ten `normal` 9-iron shots, followed by ten with less spin and ten with more spin whilst not changing distance relative to the `normal` shots. A passive-marker motion-capture system and Doppler radar device were used to track clubhead presentation and ball flight respectively. ANOVA revealed that, as a group, players were able to significantly reduce spin relative to the `normal` shots without affecting distance, but were unable to increase spin. Greater variability was seen amongst shots whereby players were attempting to influence spin. A subsequent regression analysis revealed that clubhead speed, spin loft and vertical impact location significantly contributed to the prediction of spin, whereas horizontal impact location and face-to-path angle did not.